Proceedings of the Joint Workshop on Social Dynamics and Personal Attributes in Social Media 2014
DOI: 10.3115/v1/w14-2706
|View full text |Cite
|
Sign up to set email alerts
|

Self-disclosure topic model for Twitter conversations

Abstract: Self-disclosure, the act of revealing oneself to others, is an important social behavior that contributes positively to intimacy and social support from others. It is a natural behavior, and social scientists have carried out numerous quantitative analyses of it through manual tagging and survey questionnaires. Recently, the flood of data from online social networks (OSN) offers a practical way to observe and analyze self-disclosure behavior at an unprecedented scale. The challenge with such analysis is that O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Buzz communities and found that different communities (e.g., politics or sports) use profanity with varied frequencies and in different ways. Turning to Twitter, Bak et al [2] studied self-disclosure behavior in Twitter conversations. As one aspect of self-disclosure, profanity was used more frequently between users with higher relationship strength.…”
Section: Cursing On Social Mediamentioning
confidence: 99%
“…Buzz communities and found that different communities (e.g., politics or sports) use profanity with varied frequencies and in different ways. Turning to Twitter, Bak et al [2] studied self-disclosure behavior in Twitter conversations. As one aspect of self-disclosure, profanity was used more frequently between users with higher relationship strength.…”
Section: Cursing On Social Mediamentioning
confidence: 99%
“…We map each SD level to one sentiment and use the same seed words/trigrams from SECRET as in SDTM below. Used in previous work (Bak et al, 2012).…”
Section: Classification Of Self-disclosure Levelmentioning
confidence: 99%
“…However, it is hard to identify intimacy between users in large scale online social network. So we choose conversation behaviors such as conversation frequency and length which can be treated as proxies for measuring intimacy between two people (Emmers -Sommer, 2004;Bak et al, 2012).…”
Section: Relations Of Self-disclosure and Conversation Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of this kind of focus on Twitter abound. Bak et al [2012] looked at how certain kinds of content in Twitter conversations might be indicative of self-disclosure and the strength of relationship between the participants; Murnane & Counts [2014] examine the Twitter posts from smokers and the part they play in them giving up smoking; Kendall et al [2011] examine how people use Twitter to share information with one another about their health and fitness activities; Magee et al [2013] use tweets amongst players of a role-playing game to explore the part played by these in enhancing their gaming experience; Zhang et al [2011] look at how consumers use 'word-of-mouth' on Twitter to share information about businesses and their products and services; and Sleeper et al [2013] examine a range of tweets that tweeters have subsequently regretted posting and the actions they have then taken to engage in some kind of repair.…”
mentioning
confidence: 99%